Farmakokinetik Oksitetrasiklin Melalui Pemberian Intravena Dosis Tunggal pada Anjing Sehat dan Demam (PHARMACOKINETIC OF OXYTETRACYCLINE WITH INJECTION INTRAVENOUS SINGLE DOSE IN HEALTHY AND FEVERED DOGS) - Budiasa, Ketut (Jurnal Veteriner; Vol 2 No 2 (2001), 2016)
Farmakokinetik Oksitetrasiklin Melalui Pemberian Intravena Dosis Tunggal pada Anjing Sehat dan Demam   (PHARMACOKINETIC OF OXYTETRACYCLINE WITH INJECTION INTRAVENOUS SINGLE DOSE IN HEALTHY AND FEVERED DOGS)
Keywords: Pharmacokinetic; oxytetracycline; dogs; fever